Penerapan Pembelajaran Guided Inquiry untuk Meningkatkan Self-Confidence dan Pemahaman Konsep Matematika Siswa Kelas VIII SMPN 13 Mataram - Dea Annisariestaqwa; Masjudin Masjudin; sri Yuliyanti; Ade Saputra (Jurnal Kependidikan Ki Hajar Dewantara, 2025)
The purpose of this study is to describe the application of Guided Inquiry  learning that able to improve self-confidence and understanding of mathematical concepts of grade VIII students of SMP N 13 Mataram. The type of research used is classroom action research. The subjects of this study are 33 students in grade VIII/E SMP N 13 Mataram. The research instruments used consisted of teacher and student observation sheets, self-confidence  questionnaires and evaluation test sheets. Based on the learning results in the first cycle, the results of the implementation of teacher activity learning were 67.77% with the good category and the results of the percentage of student activity were 57.27% with the sufficient category, then the results of obtaining student self-confidence were 62,01% with the appropriate category, and the completeness of student learning was classically 30.30% with the low category. Meanwhile, in the second cycle, there was an increase obtained from the percentage of teacher activity of 86.60% (very good) and student activity of 80.90% (very good), while the results of student self-confidence were 93,02% (very appropriate), and the classical completeness of students was 81.82%. Based on the results of the research, the researcher in this study has increased from cycle I to cycle II. Thus, it can be concluded that through the application of guided inquiry  learning, it can increase self-confidence and understanding of mathematical concepts of students in grade VIII/E SMP N 13 Mataram